Composition and variability of phospholipids in Chinese human milk samples. (November 2020) - Li, Siming; Chen, Yujie; Han, Bin; Xu, Tao; Liu, Tongjie; Yi, Huaxi; Zhou, Xiaohong; Zhang, Lanwei; Liu, Ping; Ma, Changhong; Li, Yuanyuan; Pan, Jiancun; et al.
Abstract: Using gas chromatography and HPLC–MS/MS, 28 fatty acids and 74 molecular species of phospholipid were identified in 90 mature (96–180 days) human milk samples from three regions of China (Zhengzhou, Wuhan and Harbin). There were obvious differences in the content of some phospholipid fatty acids from three regions. The differences in fatty acid composition of human milk phospholipids in different individuals were mainly reflected in the contents of unsaturated fatty acids. The molecular species with the highest content of glycerophospholipids in human milk samples tested were 36:2. The molecular species of sphingomyelin in human milk from the three regions differed greatly, but the glycerophospholipid composition did not differ significantly. Compared with glycerophospholipid, the contents of molecular species in human milk sphingomyelin from different individuals had a higher coefficient of variation (33.14%).